Process Mining Applied to Postal Distribution - Martínez, Víctor (2021)
Process mining is a technique that allows analyzing business processes through event logs. In this article, different process mining techniques are used to analyze data based on the postal distribution of products in the Argentine Republic between the years 2017 and 2019. The results obtained allow stating that 85% of the shipments made conform exactly to the model. The analysis of the situations with a low level of adjustment to the discovered process constituted a tool for quick identification of some recurring problems in the distribution, facilitating the analysis of the deviations that occurred. In the future, we expect to incorporate these techniques to build early notifications that warn about the existence of excessive deviations from the process.